2021
DOI: 10.1007/s11205-021-02759-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Enterprises on Individual Wellbeing in South Korea: The Moderating Roles of Social Capital in Multilevel Analysis

Abstract: Various studies have proposed social enterprise as a potential policy intervention and a policy alternative to deal with the complex problem of wellbeing enhancement. However, the relationship between social enterprise and wellbeing has not been fully expounded, particularly its impact on the local community. This study aims to empirically examine the relationship between social enterprise and the wellbeing of individuals in the local community, utilizing a multilevel framework. It further explores whether soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Thus, unless individuals are provided with a more drastic improvement in economic and vertical wellbeing, they are prone to be less satisfied, which explains the observation that developed states have lower levels of wellbeing (Giri et al, 2013;Kahneman & Deaton, 2010;Khalek, 2014;Peace, 2001). It is suggested that as a country develops, alternative forms of goods, such as nonprofit-based social enterprises, are necessary to provide economic assistance to individuals who are experiencing material difficulties (Woo & Jung, 2022).…”
Section: Vertical and Horizontal Social Inclusionmentioning
confidence: 99%
“…Thus, unless individuals are provided with a more drastic improvement in economic and vertical wellbeing, they are prone to be less satisfied, which explains the observation that developed states have lower levels of wellbeing (Giri et al, 2013;Kahneman & Deaton, 2010;Khalek, 2014;Peace, 2001). It is suggested that as a country develops, alternative forms of goods, such as nonprofit-based social enterprises, are necessary to provide economic assistance to individuals who are experiencing material difficulties (Woo & Jung, 2022).…”
Section: Vertical and Horizontal Social Inclusionmentioning
confidence: 99%
“…Through addressing local vulnerabilities that are known to favour or harm health, SEs are considered to improve public health across disadvantaged segments of the population (e.g., through provision of employment and training). In addition, they can also provide an array of programmes, products and services to populations experiencing inequalities in health [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using theories related to capability, social capital, and space of wellbeing, some studies have shown that SEs enhance health and wellbeing [4,15]. However, some argue that many of the studies showing evidence of how SEs relate to public health and wellbeing have relied on small numbers of cases and on interview data [2,16]. Furthermore, there are those who state that most of the available empirical evidence has not taken into consideration the capacities of SEs, which may directly or indirectly affect their effectiveness in supporting socially vulnerable population groups [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation